2006
DOI: 10.1002/art.22139
|View full text |Cite
|
Sign up to set email alerts
|

CTLA‐4IG suppresses reactive oxygen species by preventing synovial adherent cell–induced inactivation of rap1, a ras family GTPASE mediator of oxidative stress in rheumatoid arthritis T cells

Abstract: Objective. Oxidative stress contributes to the inflammatory properties of rheumatoid arthritis (RA) synovial T lymphocytes. This study was undertaken to investigate the mechanisms leading to production of reactive oxygen species (ROS) and oxidative stress in RA synovial T lymphocytes.Methods. ROS production in T lymphocytes from the peripheral blood (PB) of healthy donors and from the PB and synovial fluid (SF) of RA patients was measured by ROS-dependent fluorescence of 6-carboxy-2 ,7 -dichlorofluorescein. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 45 publications
(70 reference statements)
2
38
0
Order By: Relevance
“…Similar effects are observed in PB T cells chronically exposed to TNF-␣ (20,30). Additionally, stimulation of PB T cells with a number of inflammatory cytokines, in combination with CD28 ligation, can reproduce oxidative stress observed in synovial T cells (37).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Similar effects are observed in PB T cells chronically exposed to TNF-␣ (20,30). Additionally, stimulation of PB T cells with a number of inflammatory cytokines, in combination with CD28 ligation, can reproduce oxidative stress observed in synovial T cells (37).…”
supporting
confidence: 57%
“…Lysates were cleared by centrifugation at 13,000 rpm for 15 min and protein expression was analyzed by standard Western blotting procedures as previously reported in detail (37). Proteins were resolved by SDS-PAGE, transferred to polyvinylidene difluoride membrane (Bio-Rad), and blots were probed with Abs against Noxa (Imgenex), Bim (Chemicon International), Bcl-2 (Alexis), Bcl-x L (BD Transduction Laboratories), Mcl-1 (BD Biosciences Pharmingen), and ␤-actin and ERK1/2 (Santa Cruz Biotechnology).…”
Section: Sds-page and Western Blottingmentioning
confidence: 99%
“…Extracellular ROS production may influence the oxidation state of surface proteins, but endogenous sources of oxidants (e.g., mitochondria) or endosomal ROS production may play an important role in the regulation of intracellular signaling. Remans et al (244)(245)(246) have undertaken studies to determine how intracellular pathways that are associated with ROS production may be regulated. They identified that a failure of RapI to regulate the RaI-mediated increase in ROS production, which lies downstream from Ras activation, may contribute to a hyporesponsive T cell phenotype; using a Jurkat T cell line transformed to overexpress ras constructs, this group determined that following anti-CD3 driven activation of T cells, intracellular ROS levels increased, as demonstrated by dichlorofluorescein diacetate (DCF) fluorescence.…”
Section: B T Cell Activation Pathways and Ros Signalingmentioning
confidence: 99%
“…A potential role for Rap1 in human T cell-mediated autoimmune disease was first suggested by the fact that Rap1 is inactivated in RA synovial fluid T cells and that this is associated with the persistent production of reactive oxygen species (ROS) and hyper-responsive cytokine production following TCR triggering (Remans et al, 2004(Remans et al, , 2006Abreu et al, 2009). Similarly to Ras, Rap1 is activated by TCR and adhesion molecule ligation, as well as by chemokine stimulation (Minato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%